(untitled) (Bangladesh Journal of Medical Microbiology, 2017)
The prevalence of Tuberculous meningitis remains largely underestimated due to nonspecific clinical manifestation at early stages. A total of 20 CSF samples were studied from clinically suspected cases of tuberculous meningitis. All the samples were processed for ZN staining, TB culture on LJ media and TB-PCR using IS6110 and TRC4 primers by standard protocols. Of the total 20 CSF samples, 12 cases were diagnosed as TB meningitis. Most of the tuberculous meningitis cases were found positive by PCR using TRC4 primers (83.33%) followed by IS6110 primer (66.67%) and culture on L-J media(8.33%). None were found positive by ZN staining. TB-PCR usingTRC4 primer showed higher positivity than using IS6110 in detecting tuberculous meningitis, since some strains of MTB may lack the IS6110 element in their genome. PCR assay using TRC4 primer is superior in diagnosing tuberculous meningitis. This study was aimed to evaluate the diagnostic potentials of CSF polymerase chain reaction (PCR) by using TRC4 and IS6110 primers. Further the results were also compared with culture on Lowenstein-Jensen (LJ) media and AFB smear by Zeihl-Nelson (ZN) staining. Bangladesh J Med Microbiol 2014; 08 (02): 19-22